Construction and Standardization of Successful Intelligence Test in Elementary Students - Amiri, Khadijeh (International Journal of Education and Cognitive Sciences, 2022)
The aim of this study was to construct and standardize a successful intelligence test for elementary students.The method of the present study was correlational descriptive research in terms of method of data collection and mixed research in terms of method and applied research in terms of purpose. The population of the present study included all elementary school students in the fifth and sixth years of primary schools in Tehran's District 5 who were selected using stepwise cluster sampling. In the tools development phase, the theoretical content of successful intelligence was first extracted and analyzed from Sternberg theory using content analysis method and approved by cognitive experts using Delphi Moore method. Then, based on the extracted content, the basic items of the above tool were prepared. After completing the questionnaires, 384 questionnaires were coded after removing the incomplete questionnaires, and their data were analyzed using SPSS software.The results of statistical analysis showed that the successful intelligence test had 18 items and four skills (memory-based, creative, analytical, practical skills) that the validity and reliability of the above tool was confirmed using heuristic and confirmatory factor analysis. .The results showed that according to the unique environmental conditions and context of Iran, the above tools in terms of subcomponents had appropriate validity and reliability for elementary students and in addition to increasing the educational status of students, their study is purposeful. Be meaningful and help students draw a broader plan and a stronger meaning of life for